2015
DOI: 10.1093/jb/mvv074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trastuzumab interchain disulfide bond cleavage on Fcγ receptor binding and antibody-dependent tumour cell phagocytosis

Abstract: The Fc domain of human IgG1 binds to Fcc receptors (FccRs) to induce effector functions such as phagocytosis. There are four interchain disulfide bonds between the H and L chains. In this study, the disulfide bonds within the IgG1 trastuzumab (TRA), which is specific for HER2, were cleaved by mild S-sulfonation or by mild reduction followed by S-alkylation with three different reagents. The cleavage did not change the binding activities of TRA to HER2-bearing SK-BR-3 cells. The binding activities of TRA to Fcc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…The functional roles of allosteric disulfide bonds in blood and cancer cells have been extensively reviewed by Hogg et al [3, 21]. A recent report showed that reduction and alkylation of some disulfide bonds in rituximab and trastuzumab, IgG1-based drugs, increased the binding affinity of the modified drug to some Fc gamma receptor isotypes [22, 23], but also led to decreased binding to other Fc gamma receptors [23]. In some cases, mutation of Cys residues involved in disulfide bonds may have no effect on the protein’s biological activity, as is the case of an anti-CD44 IgG2 antibody where Cys to Ser mutations led to structural changes but had no impact on the binding of the protein to receptors and to complement C1 [24].…”
Section: Introductionmentioning
confidence: 99%
“…The functional roles of allosteric disulfide bonds in blood and cancer cells have been extensively reviewed by Hogg et al [3, 21]. A recent report showed that reduction and alkylation of some disulfide bonds in rituximab and trastuzumab, IgG1-based drugs, increased the binding affinity of the modified drug to some Fc gamma receptor isotypes [22, 23], but also led to decreased binding to other Fc gamma receptors [23]. In some cases, mutation of Cys residues involved in disulfide bonds may have no effect on the protein’s biological activity, as is the case of an anti-CD44 IgG2 antibody where Cys to Ser mutations led to structural changes but had no impact on the binding of the protein to receptors and to complement C1 [24].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the affinity of trastuzumab for its target antigen were unchanged following chemical (DTT) reduction and subsequent alkylation, whereas for rituximab, they were slightly increased (44, 45). Here, using more physiologically relevant enzymatic Trx reduction, we see a similar trend of increased antigen binding for rituximab and no change in antigen binding for trastuzumab, again indicating that the same disulfide bonds are reduced by DTT and Trx.…”
Section: Discussionmentioning
confidence: 99%
“…One end of FccR could combine with immune cells, while the other end with specific antibodies, thus triggering a series of functions of cellular effector molecules, like phagocytosis, antibody-dependent cell-mediated cytotoxicity, the production of super-oxygen ions, antigen presentation, the releasing of cytokines and the generation of regulatory antibodies [12][13][14][15]. According to their affinity to IgG subtypes, FccR could be categorized into FccRI, FccRII and FccRIII, with the middle one showing low affinity to IgG [16]. Based on its function, FccRII could be further classified into three subtypes, A, B and C [17].…”
Section: Introductionmentioning
confidence: 99%